Perasaan Mahasantri Dalam Menjalankan Shalat Berjamaah Tepat Waktu Diasrama Putri Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Yulanda Yulanda (ISTISYFA: Journal of Islamic Guidance and Counseling, 2025)
This study aims to describe the emotional experiences of mahasantri in performing congregational prayers on time at the Female Dormitory of UIN Fatmawati Sukarno Bengkulu. This phenomenon is important to examine because congregational prayer in a dormitory setting is not only a form of ritual obedience but also an emotional experience influenced by institutional rules, religious motivation, and social dynamics among the students. This research employs a descriptive qualitative approach, using in-depth interviews and transcript analysis as the primary data collection techniques. The analytical procedures consist of open coding, axial coding, and selective coding to identify relevant categories and thematic patterns. The findings indicate that mahasantri experience a variety of emotions when performing congregational prayers on time. Dominant positive feelings include calmness, relief, happiness, and pride. Wulan stated that she felt “calm and not pressured during the Sunday evaluation,” while Maya expressed that she felt “more proud of myself” after consistently praying on time. Furthermore, Sella described her congregational prayer experience as “happy… the atmosphere feels different, it really feels like being at the pesantren.” However, the study also found negative emotions such as anxiety and fear of punishment when students were late or failed to join the congregational prayer, as expressed by Sella who felt “anxious… afraid of being punished.” Another finding shows that some students experienced an emotional shift from feeling forced to becoming sincere, as reflected in Wulan’s statement: “At first it felt forced… over time I got used to it… eventually I became sincere.” Overall, this study concludes that the emotional experiences of mahasantri in performing congregational prayers on time span a wide emotional spectrum and are influenced by a combination of internal and external factors. Congregational prayer functions not only as a ritual activity but also as a medium for building discipline, spiritual comfort, and emotional development within the dormitory environment.